(untitled) (JS (JURNAL SEKOLAH), 2020)
Abstract:One of the duties of the Principal is to carry out supervision in schools which is his responsibility. To carry out effective classroom observation supervision requires conceptual, interpersonal and technical skills. One of the efforts made by the principal in improving the quality of education is through improving the performance of teachers in the teaching and learning process which is carried out through coaching the supervision of principal class observations. The purpose of this school action research is to determine the extent to which the increase in teacher performance in implementing effective learning in SD Negeri 116251 through classroom observation supervision. In this action research carried out in 3 cycles, the results of the actions taken are proven to improve teacher performance by achieving ideal standards. From 58.53% in cycle 1, it can increase to 68.24% in cycle 2, and cycle 3 increases to 80.88%. The results of this school action research indicate that the application of principal observation supervision can improve teacher performance by reaching 100% completeness. The teacher’s response was very positive to the coaching carried out by the principal through classroom supervision. Keywords: Teacher Performance, Effective Learning, and Classroom Observation Supervision Abstrak:Salah satu tugas Kepala Sekolah adalah melaksanakan supervisi di sekolah yang menjadi tanggung jawabnya. Untuk melaksanakan supervisi observasi kelas secara efektif diperlukan keterampilan konseptual, interpersonal dan teknikal. Salah satu upaya yang dilakukan oleh kepala sekolah dalam meningkatkan mutu pendidikan adalah melalui peningkatan kinerja guru dalam proses belajar mengajar yang dilakukan melalui pembinaan supervisi observasi kelas kepala sekolah. Tujuan dari penelitian tindakan sekolah ini adalah untuk mengetahui sejauh mana peningkatan kinerja guru dalam melaksanakan pembelajaran yang efektif di SD Negeri 116251 Aek Batu melalui supervisi observasi kelas. Dalam penelitian tindakan ini dilakukan dalam 3 siklus, dari hasil tindakan yang dilakukan terbukti dapat meningkatkan kinerja guru dengan mencapai standar ideal. Dari 58,53 % pada Siklus l, dapat meningkat menjadi 68,24 % pada siklus 2, dan siklus ke 3 meningkat menjadi 80,88%. Hasil penelitian tindakan sekolah ini menunjukkan bahwa penerapan supervisi observasi kelas kepala sekolah dapat meningkatkan kinerja guru dengan ketuntasan mencapai 100 %. Tanggapan guru adalah sangat positif terhadap pembinaan yang dilakukan kepala sekolah melalui supervisi observasi kelas. Kata Kunci: Kinerja Guru, Pembelajaran Efektif, dan Supervisi Observasi Kelas